The Implementation of Jigsaw Learning in Improving VII Grade Students’ Achievement MTsN Kedungharjo Mantingan for Sejarah Kebudayaan Islam Subject - Nida Aqillah; Ifa Rodifah Nur (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
In the teaching and learning process, teachers have an important position and determinator whether or not the learning process success. The choice of appropriate learning method also need to be noticed by the teachers. Giving something new in the learning model will improve students’ spirit and achievement. One of the learning method is by implement the cooperative method which consists of various learning methods with group system. Then, the small groups are able to build students’ togetherness and resposibility between them. The implementation of the method is this research was done in two steps and it is usually called as cycle. Every cycle consist of four steps; (1) planning, (2) acting, (3) observing, (4) reflecting. The result of the research showed that there is an improvement in students’ achievement toward Sejarah Kebudayaan Islam subject using jigsaw method. It is indicated that the implementation of jigsaw learning for Sejarah Kebudayaan Islam subject of grade V MTsn is effective in improving students’ achievement.